Assessment of trade integration patterns between the Russian federation and East Asian economies using panel-gravity framework - Ehsan Rasoulinezhad; Farhad Taghizadeh-Hesary; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2019)
This study is the first attempt to investigate the patterns of imports and exports between the Russian Federation and East Asian economies, namely, the People's Republic of China; Hong Kong, China; Macau, China; Japan; the Republic of Korea; and Mongolia. To this end, a panel-gravity trade model with series over 2001 to 2017 is provided to estimate the gravity variables in our models. The results revealed that gross domestic product (GDP) and income are more important in export patterns from the Russian Federation to the East Asia region, meaning that economic size and the income of population in East Asian economies are more essential in this pattern, compared to other variables. Moreover, the Russian Federation's export pattern with the East Asia region follows the hypothesis of Linder (1961), while the Russian Federation's import pattern with this region is in line with the Heckscher-Ohlin (H-O) hypothesis.
Keywords: C21; C23; F10; F14; 330; foreign trade pattern; disaggregated trade data; Russian Federation; East Asia region; gravity model